ANALISIS BIAYA DAN PEMASARAN DALAM PERENCANAAN LABA PT. MITRA JERUK LESTARI TEBAS KABUPATEN SAMBAS - yarso, Poniam; Matsum, Junaidi H.; Asriati, Nuraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to analyze: (1) PT. Mitra Jeruk Lestari (MJL) in Tebas District, Sambas Regency. (2) Marketing of PT. Mitra Jeruk Lestarai (MJL) in Tebas District, Sambas Regency. (3) PT. Mitra Jeruk Lestarai (MJL) in Tebas District, Sambas Regency. The research method used in this study is a mixed method (mixed method), namely quantitative and qualitative research. The data is through data collection techniques using communication techniques, observation techniques, and documentary study techniques and data analysis techniques used through the stages of data reduction, data verification, and data analysis. As for checking the validity of the data through source triangulation, technical triangulation, and time triangulation. The results showed that: (1) Costs at PT. Mitra Jeruk Lestari has increased. An increase in maintenance costs, production salaries, on variable costs an increase in the cost of raw materials, while the cost of the factory everhead due to an increase in fuel costs (BBM). (2) Marketing of PT. Mitra Jeruk Lestari includes 4P: Product (Price), Price (Price), Place (Place), Promotion (Promotion). (3) Profit planning in 2019 is planned to be a profit of 25% with total sales of Rp. 555,114,687, Analysis in 2020 planned profits to 50% with total sales of Rp. 832,672,030. Keywords : Cost, Marketing, Profit planning